O my_iach a l'ud'och play still - J. Nemcakoua:::Creator::::::::::::
The Slovakian production of Of Mice and Men, held at Slovenske Narodne Divadlo in Bratislava, Slovakia. From left: George (Peter Trnik) and Lennie (Milan Bahul)